1986
DOI: 10.1530/jrf.0.0780353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold and hot ambient temperatures on plasma progesterone concentrations in ewes with intact and denervated ovaries containing experimentally maintained corpora lutea

Abstract: Summary. Twenty ewes in which maintained corpora lutea had been established were subject to 1 of 3 treatments: denervation of the ovaries by freezing, denervation of the ovaries using the chemical 6-hydroxydopamine, or control. The animals were exposed sequentially to normal (24\ m=. \ 5\ s=deg\ C), cold (10\ m=. \ 7\ s=deg\ C), normal (23\ m=. \ 8\ s=deg\ C), hot (39\ m=. \ 4\ s=deg\ C) and normal (24\m=.\6\s=deg\C)temperatures, each for 1 week. On the final 3 days of exposure rectal temperatures and heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Since propranolol has no direct action, and works rather by blocking the adrenergic receptor from stimu¬ lation by the endogenous neurotransmitter or administered agonists, the reduction in the pro¬ gesterone secretion rate in response to propranolol described here suggests that the measured pre-infusion secretion rate was itself the consequence of endogenous, physiological adrenergic stimulation. This agrees with the earlier observation of decreased peripheral progesterone concen¬ trations in sheep with denervated ovaries (Wheeler & Blackshaw, 1986). Presumably therefore, variation in the activity of the autonomie sympathetic nervous system has an effect similar to that produced by the drugs used here, increasing sympathetic tone increasing adrenergic neurotrans¬ mitter (principally noradrenaline) and adrenal medulla hormone (principally adrenaline) release and consequently ovarian progesterone secretion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Since propranolol has no direct action, and works rather by blocking the adrenergic receptor from stimu¬ lation by the endogenous neurotransmitter or administered agonists, the reduction in the pro¬ gesterone secretion rate in response to propranolol described here suggests that the measured pre-infusion secretion rate was itself the consequence of endogenous, physiological adrenergic stimulation. This agrees with the earlier observation of decreased peripheral progesterone concen¬ trations in sheep with denervated ovaries (Wheeler & Blackshaw, 1986). Presumably therefore, variation in the activity of the autonomie sympathetic nervous system has an effect similar to that produced by the drugs used here, increasing sympathetic tone increasing adrenergic neurotrans¬ mitter (principally noradrenaline) and adrenal medulla hormone (principally adrenaline) release and consequently ovarian progesterone secretion.…”
Section: Discussionsupporting
confidence: 92%
“…The antiserum ( 11P27; Fanti & Wang, 1984) had cross-reactions of 100% with proges¬ terone, 96% with 1 la-hydroxyprogesterone, 11 % with 5a-pregnane-3,20-dione, 4% with 6ß-hydroxyprogesterone, 1 % with pregnenolone, and < 1 % with 20ß-dihydroprogesterone, 17-hydroxyprogesterone and androstenedione; no other steroid cross-reacted at >0T%. The progesterone radioimmunoassay method has been described elsewhere (Wheeler & Blackshaw, 1986). The efficiency of extraction was 80-6 ± 2-28% (n = 38).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports have suggested that the plasma concentration of progesterone is influenced by environmental factors [23,24] and nutritional conditions [25,26] in ruminant animals. However, in the present study, the plasma concentrations of progesterone in the low P group were maintained at around 1 ng/ml, and this is similar to the level observed in abnormal conditions, such as ovarian disorders [9], stress [10], and luteal hypoplasia of Shiba goats [unpublished results].…”
Section: Discussionmentioning
confidence: 99%
“…The progesterone radioimmunoassay method has been described by Wheeler & Blackshaw (1986) and the antiserum (11P27) by Fanti & Wang (1984). The efficiency of extraction from ovine plasma was 83-3 + 1-46% (mean ± s.e.m., « = 53).…”
Section: Progesterone Concentrationsmentioning
confidence: 99%